Risk factors of recurrent abdominal pain in adolescents - Muzal Kadim; Anjar Setiani; Aryono Hendarto (Indonesian Pediatric Society, 2021)
Background Recurrent abdominal pain is 2-4% of all cases encountered by pediatricians. Risk factors vary among countries. There is no data on prevalence and risk factors of recurrent abdominal pain in adolescents in Indonesia. Objective To evaluate prevalence and risk factors of recurrent abdominal pain in junior high school students. Methods A cross-sectional study was performed among junior high school students in South Jakarta who experienced recurrent abdominal pain according to Roma III criteria. Students allowed by their parents to participate to this study were asked to complete a Roma III questionnaire. Data about sociodemographic and history of recurrent abdominal pain among the parents were also collected using a questionnaire. ResultsThree hundred ninety-six adolescents participated in this study, 17.2% among them experiencing recurrentabdominal pain. Irritable bowel syndrome (IBS) was the most common type (42.6%), followed by functional dyspepsia (30.9%), functional abdominal pain syndrome (11.8%), functional abdominal pain (10.3%), and abdominal migraine (4.4%). The risk factor most responsible was anxious personality (OR 3.86; 95%CI 2.05 to 7.29, P<0.001). Other risk factors that contribute were female, age > 13 years, and middle to lower family income. Conclusions Prevalence of recurrent abdominal pain in adolescents is 17.2%. Irritable bowel syndrome is the most common type. The risk factors are anxious personality, female, age > 13 years, and middle to lower family income.